Lid-parallel conjunctival folds (LIPCOF) and dry eye: a multicentre study. Issue 11 (5th September 2012) - Németh, János; Fodor, Eszter; Lang, Zsolt; Kosina-Hagyó, Krisztina; Berta, András; Komár, Tímea; Petricek, Igor; Higazy, Mohamed; Prost, Marek; Grupcheva, Christina; Kemer, Ozlem Evren; Schollmayer, Petra; et al.
Abstract : Aims: The study was designed to test the clinical application of the grading of lid-parallel conjunctival folds (LIPCOF) as a diagnostic test for dry eye. Methods: At 12 centres in 11 countries, 272 eyes of 272 dry eye patients (75 men, 197 women) were examined. Their mean age was 52.7±16.2 years. The LIPCOF were graded according to the method of Höh et al. The tear film break-up time (BUT) was measured, and fluorescein staining and the Schirmer 1 test were performed. The subjective symptoms were evaluated by 16 questions. Results: The LIPCOF score demonstrated significant positive correlations with age, dry eye disease severity and fluorescein staining (r>0.2, p<0.001), and negative correlations with BUT and results of the Schirmer 1 test (r<–0.2, p<0.001). The LIPCOF score exhibited a significant correlation with the overall subjective symptoms (r=0.250, p<0.001). The sensitivity and specificity of LIPCOF grading for discriminating between normal and dry eyes were best with the cut-off between LIPCOF degrees 1 and 2. Conclusions: The displayed medium sensitivity and specificity, and good positive predictive value of the LIPCOF test support the use of LIPCOF grading as a simple, quick and non-invasive dry eye screening tool.